The Implementation Model Of Universal Health Coverage Management - Serlianti, Lovitta; Novira, Daisy; Rohani, Tuti (Universitas Dehasen Bengkulu, 2025)
The purpose of this research is to identify the supporting factors and inhibiting factors in the implementation of universal health coverage in North Bengkulu Regency. Specifically, this research provides novelty to the focus on building an implementation model for the implementation of universal health coverage. The method in this study used a qualitative method using a case study approach. The findings in this study are the best model in the implementation of universal health coverage at the district level, namely comprehensive population coverage, essential health service packages, financial protection, a strong and efficient health system, high quality health services, community participation, justice and equality, sustainable financing. Especially for sustainable financing, the Social Security Provider Agency for health must be proactive in the planning and budgeting stages of the regional revenue and expenditure budget and must ensure that the proposed funding needs for universal health coverage programs are integrated in the local government work plan for the following year.